Macro-scale boundary controls on the fluvial geomorphology of floodplain wetlands across South Africa’s hydroclimatic regions - Chemaly, Hannah Frances (Stellenbosch : Stellenbosch University, 2025)
Thesis (MA)--Stellenbosch University, 2024.